Fundamentals of drug development - Barrett, Jeffrey S. (John Wiley & Sons, Inc., 2022)
"This book discusses how to conduct pharmaceutical research and the context for how the industry fits into global healthcare. Holistically, the well-qualified author helps readers and students of drug development appreciate the time and expense of the process. Specifically, the work identifies the emerging trends shaping the future of drug development, along with important related topics like generic drugs, data sharing, and collaboration. To aid in seamless reader comprehension, the book includes a glossary of terms and a self-assessment quiz for each chapter at the end. PowerPoint slides are also available as an online ancillary for adopting professors"--